Serviço social e projeto ético-político profissional: contributos da extensão universitária - Ferraz, Anita Pereira [UNESP] (2013)
The text here presented intends to contribute for the debate around Social Work, its professional ethical and political project and university's extension, considering some of the interfaces involved on this matter. Extension's conception here adopted comprehends its educative, cultural and scientific dimensions, undisjoinabled associated to teaching and research, according to a perspective that defends the possibility of a fecund and modifying relation between university and society. With this in mind, this study included bibliographical research and eleven interviews with social workers graduated on UNESP/Franca who participated of groups of extension such as Núcleo Agrário Terra e Raiz (NATRA) and Grupo de Alfabetização Paulo Freire (GAPAF). The reason for choosing those groups is the political direction given to its extensional actions. This study was divided into three chapters: Social Work and the Contemporary Debate around its Critical Renovation; University, Sociability, University's Extension and Communicative Dimension; and Extensional Practice, Professional Formation and Social Work's Ethical and Political Project. Four main categories were analyzed: extensional practice; university's tripod: teaching, research and extension; extension and professional exercise; extension and Social Work's political and ethical project. The study captures extension's importance to the lives of the subjects of the research, indicating the intailed relation between participation in those groups and a professional formation guided by the perspective provided for Social Work‘s political and ethical project